2010
DOI: 10.1111/j.1365-2966.2010.17267.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of galaxy cluster X-ray scaling relations

Abstract: We use numerical simulations to investigate, for the first time, the joint effect of feedback from supernovae (SNe) and active galactic nuclei (AGN) on the evolution of galaxy cluster X-ray scaling relations. Our simulations are drawn from the Millennium Gas Project and are some of the largest hydrodynamical N-body simulations ever carried out. Feedback is implemented using a hybrid scheme, where the energy input into intracluster gas by SNe and AGN is taken from a semi-analytic model of galaxy formation. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
109
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(136 citation statements)
references
References 126 publications
(224 reference statements)
25
109
1
1
Order By: Relevance
“…The only exception is the LX-M∆ relation, which seems to show a negative evolution. A similar level of evolution can be obtained in hydrodynamical simulations of the intracluster medium by including additional radiative cooling and uniform preheating at high redshift as a simple model of non-gravitational heating from astrophysical sources (Ettori et al 2004a;Short et al 2010;Reichert et al 2011).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The only exception is the LX-M∆ relation, which seems to show a negative evolution. A similar level of evolution can be obtained in hydrodynamical simulations of the intracluster medium by including additional radiative cooling and uniform preheating at high redshift as a simple model of non-gravitational heating from astrophysical sources (Ettori et al 2004a;Short et al 2010;Reichert et al 2011).…”
Section: Discussionmentioning
confidence: 56%
“…They found that the energy output from SNe and AGNs as implemented through semi-analytic models of galaxy formation causes a positive evolution. On the other hand, simulations based on a pre-heating model where an entropy floor of 200 keV cm 2 is introduced at z = 4 confirmed the presence of a negative evolution (Short et al 2010).…”
Section: Lx-m∆mentioning
confidence: 93%
See 1 more Smart Citation
“…Hence observational constraints have the potential to constrain the non-gravitational physics. However, Short et al (2010) point out that a statistically meaningful comparison with observations is impossible at the moment, because the largest samples of high-redshift clusters currently available are still affected by strong selection biases.…”
Section: Evolutionmentioning
confidence: 99%
“…Planelles et al (2013) further showed that AGN feedback in their simulations is capable of reproducing observed cluster baryon, gas and star fractions. Short et al (2010) included AGN feedback into cosmological simulations using a semi-analytic galaxy formation model to infer the heating rates from the full galaxy population and showed that such a model could reproduce a range of X-ray cluster properties, although they neglected the effects of radiative cooling (however, see also Short, Thomas & Young 2013). McCarthy et al (2010McCarthy et al ( , 2011 simulated the effects of AGN feedback in galaxy groups and showed that they could reproduce a number of their observed properties.…”
mentioning
confidence: 99%